Reversible hepatic decompensation following cessation of antiretroviral therapy in a patient with HIV and hepatitis C co-infection. (September 2014) - Croucher, Adam P; Main, Janice
We report the case of 47-year-old man with HIV and hepatitis C virus-associated cirrhosis who, following discontinuation of his antiretroviral therapy (ART), rapidly developed hepatic decompensation. On restarting his ART there was a noticeable improvement in his liver function, which was attributed to regaining good HIV virus control. Further data on the effects of restarting ART after ART cessation-associated hepatic decompensation are needed.